Enhancing memory performance with rTMS in healthy subjects and individuals with Mild Cognitive Impairment: the role of the right dorsolateral prefrontal cortex - Turriziani, Patrizia (Frontiers in Human Neuroscience, 2012)
A debated question in the literature is the degree of anatomical and functional lateralization of the executive control processes sub-served by the dorsolateral prefrontal cortex (DLPFC) during recognition memory retrieval. We investigated if transient inhibition and excitation of the left and right DLPFC at retrieval by means of repetitive transcranial magnetic stimulation (rTMS) modulate recognition memory performance in 100 healthy controls (HCs) and in eight patients with Mild Cognitive Impairment (MCI). Recognition memory tasks of faces, buildings, and words were used in different experiments. rTMS-inhibition of the right DLPFC enhanced recognition memory in both HCs and MCIs. rTMS-excitation of the same region in HCs deteriorated memory performance. Inhibition of the right DLPFC could modulate the excitability of a network of brain regions, in the ipsilateral as well as in the contralateral hemisphere, enhancing function in HCs or restoring an adaptive equilibrium in MCI.